The Role and Strategy of Mitra Sharia Cooperatives in Promoting MSME Growth - Fidat, Faizatul; Rolianah, Wiwik Saidatur (JURNAL ISLAM NUSANTARA, 2023)
This research aims to analyze the role and strategy of the MUI Sharia Cooperative in developing MSMEs after partnering with it. The approach used in this study is a qualitative method with descriptive analysis. Information was obtained through direct interviews with informants who act as Micro, Small and Medium Enterprises (MSMEs) actors. The research results reveal that the MUI Sharia Cooperative implements an MSME development strategy focusing on products by implementing simple conditions and buying and selling prices that comply with Islamic law. The distribution strategy is carried out by visiting members and grouping them in one area to make it easier for members to access transactions. The promotional strategy is carried out by creating brochures and banners as selling points and attractions. The development of MSMEs after joining the MUI Sharia Cooperative has increased because the more the business develops, the greater the income generated. The role of the MUI Sharia Cooperative in developing MSMEs is realized in providing financing to business actors by demonstrating good quality service performance.